Transformasi Digital Birokrasi dalam Perspektif Good Governance di Kabupaten Bangli - I Putu Indra Paramarta; I Nyoman Subanda (Dinasti Research, 2026)
This study aims to analyze bureaucratic digital transformation through the implementation of ASN Digital from a good governance perspective at the Regional Personnel and Human Resource Development Agency of Bangli Regency, identify the factors influencing its implementation, and examine its impact on personnel services. This study employed a descriptive method with a qualitative approach. Data were collected through observation, in-depth interviews, and documentation studies, and were analyzed using data reduction, data display, and conclusion drawing techniques. Data validity was ensured through source, technique, and time triangulation. The results indicate that ASN Digital has supported bureaucratic digital transformation and the implementation of good governance at BKPSDM Bangli Regency through the principles of transparency, participation, rule of law, and accountability. Transparency is reflected in information openness and integrated services, participation is demonstrated through the active involvement of civil servants, the rule of law is supported by clear regulations, and accountability is manifested through a documented system that can be monitored in real time. The implementation of ASN Digital is supported by information openness, civil servant participation, regulatory support, and an integrated supervision system. However, several challenges remain, including limited computer facilities, human resource constraints, incomplete administrative requirements, and system maintenance. Overall, ASN Digital has positively contributed to improving the transparency, effectiveness, efficiency, and accountability of personnel services in Bangli Regency.